The Effect of Problem-Based Learning Model on The Critical Thinking Skills of Students at State Senior High School 2 Ranah Batahan in The Subject of Temperature and Heat - Ramadhan, Muhammad Ikhsan (PILLAR OF PHYSICS EDUCATION, 2025)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) model in enhancing the critical thinking skills of high school students on the topic of heat and temperature. The background of the study highlights the need for learning models that foster higher-order thinking skills and provide students with opportunities to solve contextual problems. A pre-experimental research design with a one-group pretest-posttest approach was applied to a class of 29 students from SMA Negeri 2 Ranah Batahan. The instrument used was a critical thinking skill test based on five indicators proposed by Ennis: providing simple explanations, building basic skills, making inferences, providing further clarification, and developing strategies and tactics. Data were analyzed using the Shapiro-Wilk test, Levene's test, Wilcoxon Signed-Rank test, and N-Gain analysis. The results indicate a significant improvement in students' critical thinking abilities across all indicators after the implementation of PBL. The average N-Gain score reached 75.70%, categorized as high. The greatest improvement was observed in the "strategy and tactics" indicator, while the highest posttest score was in the "making inferences" indicator. These findings suggest that the PBL model, supported by interactive learning media, effectively engages students in problem-solving and reflective thinking. The model encourages active involvement, fosters logical reasoning, and improves conceptual understanding. In conclusion, the PBL approach integrated with interactive learning media is a powerful tool in promoting critical thinking in physics education.